Safety and efficacy of East Asian herbal medicine for iron deficiency anemia in children and adolescents: a systematic review and meta-analysis - Jeong, Yoon Kyoung; Kim, Jae Hyun; Lee, Sun Haeng; Bang, Miran; Chang, Gyu Tae (Frontiers in Pharmacology, 2024)
Background: This systematic review and meta-analysis aimed to evaluate the efficacy and safety of East Asian herbal medicine (HM) for iron deficiency anemia (IDA) in children and adolescents.Methods: Twelve electronic databases were searched in May 28, 2023 for randomized controlled trials (RCTs) evaluating the efficacy of HM in children with IDA. The primary outcome measures for preand post-treatment comparison with oral iron included blood hemoglobin and serum ferritin levels, whereas the secondary outcomes included the total effective rate (TER), incidence of adverse events (AEs), average healing time, and hematologic indicators related to IDA. Meta-analysis was performed using Review Manager 5.4 and R studio 4.3 software, and subgroup analyses were performed according to the different groups (type of intervention and duration of treatment). The effect size measures used were the risk ratio, mean difference, and standardized mean difference with 95% confidence intervals. The risk of bias was assessed using a revised Cochrane risk of bias tool for randomized trials, and the quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation tools.The meta-analysis included 28 studies. Five studies compared the efficacy of HM alone with that of oral iron alone, whereas 23 compared the efficacy of a combination of HM and oral iron with that of oral iron alone. The meta-analysis revealed that the HM treatment group showed significant improvements in all outcome measures compared to those observed in the oral iron group. Moreover, HM significantly reduced the incidence of gastrointestinal AE, compared to that associated with oral iron. Among the 28 studies, the most commonly used HM prescription was Xingpi Yanger Granules, and the most commonly used botanical drug was Astragali Radix, followed by Atractylodis Rhizoma Alba and Angelicae Sinensis Radix.This meta-analysis identified evidence of the efficacy and safety of HM in children with IDA. Compared to conventional oral iron therapy, HM improved IDA-related blood markers and TER, with fewer AEs and shorter mean healing times. However, further well-designed, large-scale clinical trials are necessary to strengthen the evidence of the efficacy and safety of botanical drugs.